Margaret Thatcher on leadership lessons for American conservatives today - Gardiner, Nile; Thompson, Steve 1950- (Regnery Publishing, Inc., an Eagle Publishing Company, 2013)
Margaret Thatcher's time in office defined an era - a Golden Age of conservative leadership. This book outlines the critical lessons conservatives can learn from Lady Thatcher on articulating conservative principles to a broader audience, cutting through bureaucratic messes to achieve goals, and standing up to aggressive regimes.